A simulation-optimization approach for the household energy planning problem considering uncertainty in users preferences - Rossit, Diego Gabriel (2020)
Power supply is one of the basic needs in modern smart homes. Computer-aid tools help optimizing energy utilization, contributing to sustainable goals of modern societies. For this purpose, this article presents a mathematical formulation to the household energy planning problem and a specic resolution method to build schedules for using deferrable electric that can reduce the cost of the electricity bill while keeping user satisfaction at a satisfactory level. User satisfaction have a great variability, since it is based on human preferences, thus a stochastic simulation-optimization approach is applied for handling uncertainty in the optimization process. Results over instances based on real-world data show the competitiveness of the proposed approach, which is able to compute dierent compromise solution accounting for the trade-off between these two conficting optimization criteria.